An acoustic investigation of the [ATR] feature effect on vowel-to-vowel coarticulation - Orphanidou, C (2008)
We report quantitative measurements of vowel-to-vowel coarticulation for neighbouring and non-neighbouring vowels that result from changes in the Advanced Tongue Root (ATR) feature. Native speakers of Southern British English produced utterances; we matched pairs that were identical except for a contrast of [+ATR] vs. [-ATR] on one "transmitter" vowel. From recordings, we computed an acoustic representation at the centres of the vowels, measuring the change in pronunciation associated with the change in [ATR] value. We observed a consistent coarticulatory effect two syllables after the transmitter when it was a low vowel (i.e. the /Λ/ vs. /a:/ and /ɒ/ vs. /ɔ:/ pairs), but little or no effect when the transmitter was a high vowel (i.e. the /i:/ vs. /I/ and /ʊ/ vs. /u:/ pairs). Interestingly, we observed more dramatic coarticulation on the next-nearest neighbour than on the vowel following the transmitter.